2016
DOI: 10.2147/ndt.s106989
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of facial emotion recognition, alexithymia, and levels of anxiety and depression in patients with somatic symptoms and related disorders

Abstract: BackgroundThe concept of facial emotion recognition is well established in various neuropsychiatric disorders. Although emotional disturbances are strongly associated with somatoform disorders, there are a restricted number of studies that have investigated facial emotion recognition in somatoform disorders. Furthermore, there have been no studies that have regarded this issue using the new diagnostic criteria for somatoform disorders as somatic symptoms and related disorders (SSD). In this study, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The majority of the studies confirmed reduced emotion-recognition accuracy in patients with somatoform disorders [111,125128], fibromyalgia [120], chronic facial pain [129] and temporomandibular disorders [130], compared to healthy controls. Reduced recognition performance was reported for the individual emotions of anger, joy, sadness, fear, disgust, and neutral emotions [111,120,126,127], even after controlling for alexithymia, depression and anxiety [111]. However, in contrast to those studies, one study reported a trend towards patients’ better performance in recognition of emotions, especially of angry faces [100].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies confirmed reduced emotion-recognition accuracy in patients with somatoform disorders [111,125128], fibromyalgia [120], chronic facial pain [129] and temporomandibular disorders [130], compared to healthy controls. Reduced recognition performance was reported for the individual emotions of anger, joy, sadness, fear, disgust, and neutral emotions [111,120,126,127], even after controlling for alexithymia, depression and anxiety [111]. However, in contrast to those studies, one study reported a trend towards patients’ better performance in recognition of emotions, especially of angry faces [100].…”
Section: Resultsmentioning
confidence: 99%
“…Lower emotion recognition performance was usually associated with alexithymic traits of the patients, and in some studies, the difference between patients and healthy controls diminished when alexithymia was statistically controlled. These studies suggested that emotion recognition difficulties are secondary to more basic problems, such as alexithymia or depression [127,128,130]. One interesting finding was that patients with chronic facial pain who were less accurate in recognizing emotions compared to controls were also less accurate in recognition of left/right facial movement.…”
Section: Resultsmentioning
confidence: 99%
“…9 Even in patients with acquired brain injury, facial recognition skills have been trained. 10,11,12 The present study proposes a psychophysiological treatment based on the induction of voluntary emotional facial expression to evaluate the effect of autonomic activity (nasal temperature and heart rate) in a patient with chronic pain with a high level of alexithymia.…”
Section: Pan American Journal Of Medical Thermologymentioning
confidence: 99%
“…Regarding emotion recognition, many studies show a significant alteration in patients diagnosed with mental disorders: In depression, a bias toward negative emotion has been described (41)(42)(43)(44)(45)(46) and hypothesized to be a predictor for relapse when distinctive (47,48). Altered emotion recognition was also found in patients with high levels of social anxiety (49) and in children and adults with posttraumatic stress disorder (50,51), whereas differences were no longer visible in patients with somatoform disorders when corrected for alexithymia and anxiety (52,53).…”
Section: Introductionmentioning
confidence: 99%